PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA WANITA YANG BEKERJA PADA MALAM HARI DI PT. SWARA INDAH RIAU BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Ngajulu Petrus; Mardalena Hanifah; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Labor is an important factor in a company. The company has the obligation to comply with and fulfill the rights of female workers who work at night as it is protected by the Law No. 13 Year 2003 on Manpower. PT. Swara Indah Riau does not meet workers' rights as the corresponding labor regulations that female workers to do the job is not guaranteed the security, safety and nutritious food that should be obtained from the company.The purpose of this study was to determine the rights and obligations of workers under a labor agreement against female workers who work at night in PT. Swara Indah Riau and to identify any obstacles that exist in the implementation of the legal protection of women workers in PT. Swara Indah Riau by Act No. 13 of 2003 on Manpower.This study using sociological research methods, the research force of the law covering research the effectiveness of the law, the legal impact study and research unwritten law identification with nature descriptive study that describes the rules of legal protection of women workers who work at night. Location of research at PT. Swara Indah Riau, located in Jalan Jend. Sudirman, Office complex Sudirman Raya Blok A 1-3. The data used primary data, field data taken directly from the respondents conducted through interviews and questionnaires while the secondary data were used from the legislation, books, expert opinions related to the problems. To support this research, should be set the sample population. Population is the whole or a set of objects with the same characteristics and samples are some of the characteristics of the population about to be investigated and considered to represent the entire population.The results of this research are companies make contracts that did not pay attention to Law No. 13 of 2003 on Labour and the weakness of knowledge workers in the regulation of workers' rights guaranteed by legislation. The obstacles that occur in the implementation of legal protection is the lack of budget funds, lack of understanding of the provisions of Labour legislation and Weak supervision of the Department of Manpower and Transmigration.Keywords: Legal Protection, Labor Women, PT. Swara Indah Riau